Modernization of the herbal medicine sector: Scientific research networks and capabilities in selected economies / Fung Hon Ngen - Fung , Hon Ngen (2018)
This study seeks to present a comprehensive overview of the research performance of the selected economies in relation to the herbal medicine sector. Additionally, this study aims to connect the concept of technology life cycle with the notions of convergence and UIG linkages. The study proposes that the structures of collaborative networks and comparative advantage influence the propensity for convergence in the technology life cycle which, in turn, dictates the ability of the innovation system to transition from one phase to the next. Technological convergence is defined as the unique, non-linear, complementary and cooperative step that blends incremental technology improvements from separate technological disciplines into new products that revolutionise markets (Kodama 2014). The study postulates that the herbal medicine sector transitions from one paradigm to the next as minor increments in scientific knowledge accumulate and take advantage of “windows of opportunity” to affect landscape changes in the technology life cycle. This is based on the configuration of actors in the research networks and the convergence of multiple streams of technology in developing new knowledge, and new technology. The study analyses trends in the technological life cycle in comparison with the growth in capacity in the various economies studied (Schmoch 2007). The study draws insight from case studies in Hong Kong, Malaysia, Singapore, Japan, South Korea, China and Taiwan. As the study is primarily concerned with the activity of scientists and researchers in the accumulation of knowledge and innovative capability in a science-based sector like herbal medicine, the study relies on a robust analysis of secondary data (scientific publications, patents and trademarks) as well as some qualitative data to generate the requisite insight into macro trends in the herbal medicine sector. This study first utilises broad descriptive indicators setting the scene for a global perspective of publications and patents in the herbal medicine sector, deriving inferences of the technology life cycle and patterns of convergence in the sector. This is followed by a focus on selected economies above as the most productive region; particularly measurements of growth, impact, capacity and comparative impact through indicators involving publications, patents and trademarks. The study also focuses on co-publication networks in the selected economies from East Asia. The study identified three archetypes of research network structures (university-centric, PRI-centric, and firm-centric) that are prevalent in the selected economies. The chapter also presents data projecting the core competencies in the herbal medicine sector and potential correspondence between publication and patent areas of specialisation. Qualitative insight into the configuration of research networks as well as the justification behind concerted research collaborations is also presented. Furthermore, the study also highlights the need for horizontal policies for sectoral development to transition from traditional phase to modernised phase followed by targeted policies to stimulate UIG linkages which would drive convergence in specific niche technologies.